Farmer-owned enterprises (BUMP) and stakeholder salience in the urban food system of Indonesia - GINANJAR DWI CAHYANTO; SAPJA ANANTANYU; MOHAMAD HARISUDIN (Asian Journal of Agriculture, 2026)
Abstract. Cahyanto GD, Anantanyu S, Harisudin M. 2026. Farmer-owned enterprises (BUMP) and stakeholder salience in the urban food system of Indonesia. Asian J Agric 10 (1): g100182. https://doi.org/10.13057/asianjagric/g100182. Farmer-owned enterprises (BUMP) are legally incorporated, for-profit entities that integrate community empowerment activities with business operations to promote farmer self-reliance. This study aims to examine stakeholder interests and engagement and assess the Sustainability Index and institutional status of BUMP PT. Lumpang Semar Sejahtera (BUMP PT. LSS), Central Java, Indonesia, in supporting the urban food system. This study employs a mixed-methods approach, utilizing a case study as the data collection method. The analysis employs the Stakeholder Salience Model with the NVivo 15 software. Furthermore, the assessment of the institutional Sustainability Index and status utilizes the Multidimensional Scaling analysis tool, modified by Rap-Food System. The research results indicate that BUMP PT LSS has undergone a fairly complex institutional transformation, ranging from its objectives, form, activity orientation, organizational structure, product focus, technology use, funding sources, government support, and its position in the supply chain. The shift has transitioned from a group-based social institution to a BUMP that performs both economic functions and empowerment. Bank Indonesia Representative Office for Central Java possesses a high degree of authority, legitimacy, and urgency. Sustainability assessment indicated that the social (76.64%), economic (84.31%), and institutional (77.24%) dimensions were highly sustainable, whereas the technology and environmental dimensions (72.41%) were moderately sustainable. Leverage analysis identified infrastructure availability, land conservation, membership expansion, cooperative development, and bankable financing systems as the most influential sustainability attributes. The findings demonstrate that BUMP PT. LSS contributes to strengthening urban food governance through stakeholder collaboration, farmer empowerment, and supply-chain integration. Future interventions should prioritize technological innovation and environmental sustainability to enhance the long-term resilience of farmer-owned enterprises within urban food systems.